Demonstration of CO2 Conversion to Synthetic Transport Fuel at Flue Gas Concentrations - Dowson, George R. M.; Styring, Peter (Frontiers in Energy Research, 2017)
A mixture of 1- and 2-butanol was produced using a stepwise synthesis starting with a methyl halide. The process included a carbon dioxide utilisation step to produce an acetate salt which was then converted to the butanol isomers by Claisen condensation of the esterified acetate followed by hydrogenation of the resulting ethyl acetoacetate. Importantly, the CO2 utilisation step uses dry, dilute carbon dioxide (12% CO2 in nitrogen) similar to those found in post-combustion flue gases. The work has shown a low reactivity of Grignard reagent has a slow rate of reaction in comparison to carbon dioxide, meaning that the costly purification step usually associated with carbon capture technologies can be omitted using this direct capture-conversion technique. Butanol isomers are useful as direct drop-in replacement fuels for gasoline due to their high octane number, higher energy density, hydrophobicity and low corrosivity in existing petrol engines. An energy analysis shows the process to be exothermic from methanol to butanol, however energy is required to regenerate the active magnesium metal from the halide by-product. The methodology is important as it allows electrical energy, which is difficult to store using batteries over long periods of time, to be stored as a liquid fuel that fits entirely with the current liquid fuels infrastructure. This means that renewable, weather-dependent energy can be stored across seasons, for example production in summer with consumption in winter. It also helps to avoid new fossil carbon entering the supply chain through the utilisation of carbon dioxide that would otherwise be emitted. As methanol has also been shown to be commercially produced from CO2, this adds to the prospect of the general decarbonisation of the transport fuels sector. Furthermore, as the conversion of CO2 to butanol requires significantly less hydrogen than CO2 to octanes, there is a potentially reduced burden on the so-called hydrogen economy.